2015
DOI: 10.1002/anie.201501034
|View full text |Cite
|
Sign up to set email alerts
|

CO2‐Responsive Nanofibrous Membranes with Switchable Oil/Water Wettability

Abstract: Responsive polymer interfacial materials are ideal candidates for controlling surface wetting behavior. Here we developed smart nanostructured electrospun polymer membranes which are capable of switching oil/water wettability using CO2 as the trigger. In particular, the combination of CO2 -responsiveness and porous nanostructure enables the as-prepared membranes to be used as a novel oil/water on-off switch. We anticipate that the promising versatility and simplicity of this system would not only open up a new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
191
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 293 publications
(191 citation statements)
references
References 50 publications
0
191
0
Order By: Relevance
“…18 In another example, suspended core-shell nanoparticles with adsorbed organic pollutants can lose colloidal stability and form macroscopic aggregates upon irradiation with ultraviolet light, allowing easy handling of bulkier materials as opposed to suspended nanomaterials. 4 ''Smart'' systems with hydrophobicity tunable by external signals such as pH, 19 chemical redox agent 20 and CO 2 concentration 21 have also been developed for organics-water separation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…18 In another example, suspended core-shell nanoparticles with adsorbed organic pollutants can lose colloidal stability and form macroscopic aggregates upon irradiation with ultraviolet light, allowing easy handling of bulkier materials as opposed to suspended nanomaterials. 4 ''Smart'' systems with hydrophobicity tunable by external signals such as pH, 19 chemical redox agent 20 and CO 2 concentration 21 have also been developed for organics-water separation.…”
Section: Introductionmentioning
confidence: 99%
“…ETAS is expected to show higher energy efficiencies and incur lower environmental costs than established methods for separation of neutral organics from water such as distillation, stripping, extraction, adsorption and filtration. [11][12][13] It operates at ambient temperature and pressure, requires no need for 21 -responsive systems that exhibit only two levels of hydrophobicity (i.e., merely ''on/off'' bimodal control), ETAS can achieve multiple levels of hydrophobicity and thus affinity towards organics since the electrical signal (i.e., potential) can be tuned with high precision, permitting a systematic adjustment of the ratio between the hydrophobic and hydrophilic moieties. Such flexible modulation of affinity for target pollutants is key to achieving a balance between the separation degree and the energetic efficiency, as discussed later.…”
Section: Introductionmentioning
confidence: 99%
“…Che et al reported that CO 2 -responsive surface wettability to oil/water can be realized on nanostructured electrospun poly mer (PMMA-co-PDEAEMA) membranes, which show promise as an oil/water on-off switch for controlled oil/water separation. [165] The other way to achieve gas-responsive surfaces is based on annealing a membrane in a different atmosphere. When a ZnO-nanowire-coated mesh was annealed at 300 °C in an atmosphere of oxygen and hydrogen, its surface wettability could be switched between superhydrophilic and superhydrophobic for different types of oil-water separation (i.e., waterremoval and oil-removal modes, respectively).…”
Section: Gas-responsive Surfaces For Separationmentioning
confidence: 99%
“…Therefore reversible switching of a surface state between being hydrophilic and hydrophobic is crucial, which can be achieved by engineering stimuli-responsive surfaces with well-designed nano- or microstructures. These external stimuli include electrical potential 13, 14 , temperature 15, 16 , light illumination 17, 18 , pH value 19, 20 , gas 21 , and solvent 2225 . Using solvent to control the surface hydrophilicity/hydrophobicity is a simple and practical approach.…”
Section: Introductionmentioning
confidence: 99%